2008
DOI: 10.2478/v10018-009-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of GPS/Galileo Single Frequency Ionospheric Models With Vertical Tec Maps

Abstract: ABSTRACT. The ionospheric delay is the major current source of potential range delay for single-frequency GNSS users (Kunches and Klobuchar, 2001). Single-frequency GNSS users are in most need of an ionospheric model to eliminate the ionospheric delay to a high degree of accuracy. GPS system uses the Klobuchar model for this task, which its coefficients are sent through the GPS navigation message to GPS users. Klobuchar model uses the Ionospheric Corrections Algorithm (ICA) (Klobuchar, 1987) designed to accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Alongside its applications the performances of the model have been tested in different regions from time to time. It has been shown that both versions of the model, compared to other model, are well suited for GALILEO single frequency ionospheric error correction [ Bidaine and Warnant , 2011; Radicella et al , 2008; Farah , 2008]. Jodogne et al [2004] compared the modeled vTEC (using NeQuick 1) with measurements at midlatitude regions and found good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside its applications the performances of the model have been tested in different regions from time to time. It has been shown that both versions of the model, compared to other model, are well suited for GALILEO single frequency ionospheric error correction [ Bidaine and Warnant , 2011; Radicella et al , 2008; Farah , 2008]. Jodogne et al [2004] compared the modeled vTEC (using NeQuick 1) with measurements at midlatitude regions and found good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…The eight time-varying coefficients of the model are broadcast in the GPS navigation message. GPS master control station select those coefficients from 370 possible sets of constants based on two parameters, day of the year and average solar 10.7-cm flux value (Farah, 2008).…”
Section: Gps-klobuchar Modelmentioning
confidence: 99%
“…(Dodson, 1988) concluded that the correction accuracy of the model is about 50-60% of the total delay. The model is unable to show any significant fluctuations from day to day as it assumes an ideal smooth behaviour of the ionosphere (Farah, 2008). (Newby et al, 1990) concluded also that the range error by the model can be of order of 50 m under severe ionosphere activity at low elevations.…”
Section: Gps-klobuchar Modelmentioning
confidence: 99%
“…Computation of vertical delays at an IGP using the WLS method For each IGP, the vertical ionospheric delay can be estimated using the WLS grid estimator weighted with a nominal ionospheric delay model, such as the GPS Klobuchar model or Galileo NeQuick model. 16,17) This approach estimates the vertical delay and its error bound at each grid point, allowing better monitoring of local disturbances and more robust integrity monitoring. Moreover, the WLS estimator is easy to implement and less computationally expensive than other estimators because there is no complex matrix inversion.…”
Section: Estimation Of Vertical Delays At Ippsmentioning
confidence: 99%